The Effectiveness of the Intercultural Learning Materials in Teaching English Drama - Eripuddin Eripuddin; Jufrizal Jufrizal; Agustina Agustina (AL-ISHLAH: Jurnal Pendidikan, 2022)
Teaching English drama to multicultural students has the problem of solving the similarities and differences between language and culture. This research aimed to determine the effectiveness of intercultural learning materials (ILM) in English drama at English Department. This study was quantitative research that explored quasi-experimental research. The sample of this research was eleven students in the experimental group and ten in the control group. The sample was taken by using random cluster sampling. The instrument of this research was a test that developed the student drama performance test. The data were analysed by using a T-test. The result shows that the students scored significantly in the experimental group with an average score of 201.85 % (a sig value of 0.003 0.05). Based on the result of this research, there was a significant effect of intercultural learning material in improving students' English drama. Then, the intercultural learning materials were the alternative resources for linking the different languages and cultures in teaching and learning drama.